China's policy towards North Korea during the Cultural Revolution 1966-1976 (Journal of the College of Basic Education, 2024)
During the Sino-Soviet division, North Korea became the focus of conflict and rivalry between China and the Soviet Union, as both sides tried to drag it into its axis by signing agreements with it and providing aid that North Korea desperately needed, North Korea's relationship with China has always been complex and contradictory, ostensibly linked by a common ideology, despite this, it wanted to maintain its relationship with Beijing and refrained from opposing it publicly until the Cultural Revolution, the latter and the disagreement over Pyongyang's relationship with Moscow had an impact on the decline in the relationship between the two countries, in addition to Mao's purge of many prominent Chinese Communist Party leaders.